Sporadic nonampullary tubular adenoma of the duodenum: Prevalence and patients’ characteristics - Amer A Alkhatib (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Alkhatib AA. Sporadic nonampullary tubular adenoma of the duodenum: Prevalence and patients’ characteristics. Turk J Gastroenterol 2019; 30: 111-2.